2007
DOI: 10.1111/j.1479-8425.2007.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic media before sleep can curtail sleep time and result in self-perceived insufficient sleep

Abstract: Electronic media are widespread and research has revealed connections between media use and sleep loss. In this study we aimed to elucidate how many media users get insufficient sleep and whether lengthy media use before sleep curtails sleep. Registered monitor members were surveyed twice on the Internet. The prevalence of self-perceived insufficient sleep ascribed by respondents to using electronic media before sleep was 48.0% (first survey) and 45.0% (second survey). Younger respondents more frequently ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 18 publications
7
33
1
1
Order By: Relevance
“…Associations between sleep patterns and electronic media exposure have been reported extensively in children and adolescents15,17,6368 as well as in adults 66,69. Overall, electronic media exposure in children and adolescents was most consistently associated with later bedtime and shorter sleep duration, and the presence of a media device in the bedroom was associated with increased exposure, later bedtime and shorter sleep 16,17,63.…”
Section: Lifestyle Trends Associated With Altered Sleep Patternsmentioning
confidence: 89%
“…Associations between sleep patterns and electronic media exposure have been reported extensively in children and adolescents15,17,6368 as well as in adults 66,69. Overall, electronic media exposure in children and adolescents was most consistently associated with later bedtime and shorter sleep duration, and the presence of a media device in the bedroom was associated with increased exposure, later bedtime and shorter sleep 16,17,63.…”
Section: Lifestyle Trends Associated With Altered Sleep Patternsmentioning
confidence: 89%
“…Moreover, excessive use of computers and mobile devices in the bedroom delays bedtimes and rise times. 8,9 Adolescents with four or more technological devices in their room had significantly less sleep on school nights and weekends than those with three or fewer devices. 10 As early as 2003, Van Den Bulck found that up to 1/3 of adolescents woke up from a text at least one time per month, with this trend increasing with age.…”
Section: Introductionmentioning
confidence: 97%
“…Sleep habits in college students are also very erratic, with weekday and weeknight schedules constantly shifting to meet the demands of college life. 15 Further, students who use mobile devices and social networking sites to maintain former relationships and foster new relationships in college may be at increased risk for sleep problems due to behavioral mechanisms, such as disruptions in sleep hygiene behaviors, 8 and biological mechanisms. Bright lights and active forms of technology increase physiological arousal and suppress melatonin production, therefore delaying sleep onset.…”
Section: Introductionmentioning
confidence: 99%
“…sleep (Suganuma et al, 2007) and to increased sleep disturbances (Thomée, Eklöf, Gustafsson, Nilsson, & Hagberg, 2007).…”
mentioning
confidence: 99%